Eksplorasi Etnomatematika pada Kostum Tari Lahbako - Imronita, Dinda Khusnul; Panglipur, Indah Rahayu; Putra, Eric Dwi (Media Pendidikan Matematika, 2025)
Mathematics is often perceived as an abstract discipline, detached from everyday life. However, mathematical concepts can actually be found within local cultures, one example being in the costume of Tari Lahbako, a traditional dance from Jember that represents the life of tobacco workers. This study aims to explore elements of ethnomathematics in the Tari Lahbako costume using a descriptive approach with ethnographic methods. Data were collected through direct observation and in-depth interviews at two dance studios: Sanggar Sweeta Collection and Sanggar Ninien Ariesitta. The results indicate that costume elements such as the hair bun, apron, skirt, and other accessories contain geometric shapes such as squares, circles, rhombuses, trapezoids, as well as concepts of reflection, parallel lines, and right angles. In addition, the presence of symmetrical patterns and regularity in the costume reveals an intuitive mathematical understanding by the designers. Therefore, the Tari Lahbako costume not only holds aesthetic and cultural value but also has great potential to be used as a medium for contextual mathematics learning. Through an ethnomathematical approach, students can understand mathematical concepts more concretely, meaningfully, and rooted in local wisdom